Esitysvideon tuottamisen tukeminen ohjeistuksella - Korpi, Mika (2024)
The goal of the research was to develop easy-to-use instructions for producers of videos that support learning. The broad topic was narrowed down by defining the object of the instructions, an instructional video, into a presentation video using a detailed taxonomy. The presentation video here refers to a short, concise, clearly structured, and scripted presentation spoken to the camera, to which carefully selected presentation material is synchronized to speech. Keywords, short sentences and pictures and diagrams clarifying the presentation are emphasized in the presentation material of the presentation video. The function of the presentation material is to support the presentation in the best possible way, it is not meant to be the presenter's notes or a collection of slides to be distributed to the audience. Cognitive theory of multimedia learning served as the gathering theoretical framework of the development research, which was taken towards concreteness with studies that conceptualized the production and scripting of the educational video. The study had three cycles, the first of which had three development phases and the others one. During the first cycle, a list of good presentation video design principles was derived from the theory and the first version of the checklist was compiled from them. After that, broader instructions were developed from the checklist to support the design of the presentation video. Both the checklist and the instructions were tested with three test subjects when planning a real presentation video production. In this way, the theory could be put into practice and tested fresh in the very beginning. During the second cycle, after getting to know the feedback received from the testing and, for example, the literature related to script writing, the instructions were expanded to be more detailed and especially the part of script writing was added. At the same time, the checklist was further developed and its relationship with the guidelines was considered. The new version of the checklist and instructions was tested in discussions, interviews, and observations with six test subjects. With one of them, two large presentation video productions were also made during the cycle, one in the middle stages of the cycle and the other at the end. During the third cycle, the focus was on modifying the checklist to be as concise and easy to understand as possible. Only the most essential aspects of the design of the presentation video were taken into it. To support the development of the checklist, a survey was conducted on the importance of its items to four test subjects. The broader guidelines that were involved in the development were limited to the outside of this study during the second cycle. The final development product, an artifact, was a checklist that producers of educational videos can use and further develop for their own needs.